2013
DOI: 10.1108/tlo-12-2012-0079
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning culture and leader‐member exchange quality

Abstract: PurposeIn this global era every organization aims to retain its key workers through salary, incentives, rewards and recognition. Organizational learning culture and leaders' support are amongst those aspects that have not been focused on extensively by organizations to retain their key employees. The present study aims to investigate the relationship between organizational learning culture, leader‐member exchange quality, organizational commitment and turnover intention.Design/methodology/approachA total of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 53 publications
8
53
0
Order By: Relevance
“…The positive linear effect of LCEA on job-related well-being suggests that a culture valuing quality standards, innovation and continuous improvement, as well as the expectations of external stakeholders (namely clients), contributes to workers' experience of positive affects in the workplace. This finding is in line with previous research, which found positive effects of a learning culture on workers' attitudes and feelings, such as job satisfaction (e.g., Egan et al, 2004) or commitment (Islam et al, 2013). Thus, it offers one more piece of empirical evidence that this kind of cultural orientation has positive effects, not only on performance, but also on individuals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive linear effect of LCEA on job-related well-being suggests that a culture valuing quality standards, innovation and continuous improvement, as well as the expectations of external stakeholders (namely clients), contributes to workers' experience of positive affects in the workplace. This finding is in line with previous research, which found positive effects of a learning culture on workers' attitudes and feelings, such as job satisfaction (e.g., Egan et al, 2004) or commitment (Islam et al, 2013). Thus, it offers one more piece of empirical evidence that this kind of cultural orientation has positive effects, not only on performance, but also on individuals.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, we noticed a lack of research on the consequences of a learning culture on individuals. Despite some previous research about the effects on job satisfaction (e.g., Chang & Lee, 2007;Dekoulou & Trevillas, 2015;Dirani, 2009;Egan, Yang, & Bartlett, 2004) or, for instance, on turnover intention (e.g., Islam, Khan, Ahmad, & Ahmed, 2013;Islam, Khan, & Bukhari, 2016;Joo & Park, 2010), to the best of our knowledge no previous research has been developed that seeks to understand the relationship of this kind of cultural orientation with the employees' affective well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our findings reveal that an employee's emotional bond with the organization (i.e., AC to the organization) fully mediates the positive relationship between LMX and KSB, which offers a credible description of the above "black box." While it has been suggested that high-quality LMX could elevate AC (Islam et al, 2013) and that employees' emotional bonds with the organization could be an important antecedent in predicting KSB levels (Jeung et al, 2017), the current study introduces AC as a pivotal psychological mechanism (i.e., mediator) linking LMX to KSB.…”
Section: Discussionmentioning
confidence: 83%
“…It can be said that organizational culture positively influences organizational commitment. Islam et al (2013), also concluded that when employees in an organization are faced with a culture where they can learn continuously and be supported by their superiors, they show more commitment to their organization. Acar (2012) and Gokce et al (2014), found that organizational culture has a positive relationship with organizational commitment.…”
Section: Relationship Of Organizational Culture and Organizational Comentioning
confidence: 99%